Exploring the health information seeking behavior of social media users under the background of COVID-19 pandemic: An empirical study based on social cognitive theory - Zhang, Xiaoyi; Chen, Beibei; Li, Guowang; Dong, Yueqi (Frontiers in Psychology, 2022)
With the development of the Internet healthcare platform, the awareness and convenience of users to actively seeking for health information has accelerated during the outbreak of COVID-19. In the context, social media has become one of the important platforms for users to obtain health information with its unique advantages. In order to explore the influencing factors of social media users’ health information seeking behavior, based on the research framework of social cognition theory, this paper selects six variables to construct a structural equation modeling, including information and platform quality, experience, social support, emotional arousal, self-efficacy, and social media users’ health information seeking behavior. The empirical study is carried out by collecting 219 valid questionnaires. The research results show that: (1) Information and platform quality, and use experience have a significant positive effect on emotional arousal; (2) Experience, social support, and emotional arousal have a significant positive effect on self-efficacy; (3) Emotional arousal and self-efficacy have a significant positive effect on social media users’ health information seeking behavior. The research provides an important theoretical reference for social media users and operators to cope with the huge demand for health information in the post-COVID-19 era.